Pengaruh Biaya Pendidikan dan Motivasi terhadap Pilihan Berkarir di Bidang Perpajakan - Antas, Tarsisius Angkasa (Ikatan Da'i Indonesia, 2022)
This study aims to determine the effect of perceptions of education costs, social motivation, and career motivation on career choices in the field of taxation with interest in participating in tax brevet as an intervening variable. This research method is a survey research method. This data collection was done by distributing questionnaires using google form. This research uses data analysis method using SmartPLS software version 3.0. This research was conducted on 100 respondents, namely students of the Accounting S1 Program at several universities in the Special Region of Yogyakarta that have a tax Brevet training program. The results showed that the perception of the cost of education, social motivation, and career motivation had a positive effect on interest in following tax brevet. Perceptions of education costs and social motivation have no effect on career choices in taxation. Career motivation has a positive effect on career choices in taxation. Interest in following the tax brevet does not affect the choice of a career in taxation. Perceptions of education costs, social motivation, and career motivation have no effect on career choice in taxation through interest in following tax brevet as an intervening variable.